Monitoring of PV Performance Using LabVIEW - Siti Amely Jumaat; Ammar Syahmi Bin Mohd Anuar; Mohd Noor Abdullah; Nur Hanis Radzi; Rohaiza Hamdan; Suriana Salimin; Muhammad Nafis bin Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This project aims to design a simulator for PV monitoring using LabVIEW. This project will be divided into two parts ; software where LabVIEW and Arduino IDE been contracted and hardware parts. First part involves the software development. In this project, LabVIEW program is used as the main program to monitor the output of solar panel; voltage, current, power and temperature in real time. Next, the Arduino IDE program is used to interact the sensors with the Arduino board. The Arduino Uno microcontroller board is used as data acquisition medium to collect data from the solar panel. Second, the hardware part which is PV panel setup and measurement circuit that consist of sensors and Arduino board so that the sensors data will transfer and display to the PC connected. In this simulator, the sensors are connected to the Analog I/O of Arduino Uno microcontroller which read the analogue input of sensors. The Arduino then is connected to the PC program LabVIEW to display the I-V graph and P-V graph. To make the data more significant, the data will be collected at the location 1.8635° N, 103.1089 ° E which is in Parit Raja, Batu Pahat, Johor. The data was collected with 3 different day and time; 12PM, 1PM and 2PM on 28/11/2017, 29/11/2017 and 30/11/2017.